Macroeconomic determinants of crime In Malaysia / Nur Fairuz Husna Zulkefli - Husna Zulkefli, Nur Fairuz (Universiti Teknologi Mara Perlis, 2020)
The purpose of this study is to contribute to the economic literature by providing further evidence on the impact of macroeconomic determinants of crime in Malaysia. This research is novel given the fact that not many researchers have been done in Malaysia. In this study are to investigate the relationship between selected independent variable such as poverty (POV), inflation (INF), unemployment (UNEMP) and human capital (HC) with dependent variable which is crime. This study used E-View includes, Augmented Dickey Fuller test and Philips Perron test. The finding indicates that inflation, unemployment and human capital is significant positive relationship while poverty is insignificant positive relationship towards crime. So in this paper is to identify which independent variable is the most elastic towards crime in Malaysia.